How can cervical screening meet the needs of vulnerable women? A qualitative comparative study with stakeholder perspectives from seven European countries - Partha Basu; Martin McKee; Adriana Băban; Marc Bardou; Ana Fernandes; Margarida Teixeira; Rebecca Moore; Nuno Lunet; David Ritchie; Romeu Mendes; Eric Lucas; Paolo Giorgi Rossi; et al. (BMJ Open)
Objective This study explored and compared stakeholder perspectives on enhancements to cervical cancer screening for vulnerable women across seven European countries.Design In a series of Collaborative User Boards, stakeholders were invited to collaborate on identifying facilitators to improve cervical cancer screening.Setting This study was part of the CBIG-SCREEN project which is funded by the European Union and targets disparities in cervical cancer screening for vulnerable women (www.cbig-screen.eu). Data collection took place in Bulgaria, Denmark, Estonia, France, Italy, Portugal and Romania.Participants Represented stakeholders at various levels, including user representatives (vulnerable women), healthcare professionals, social workers, programme managers and decision makers.Methods 14 meetings lasting 2 hours each were held in these seven countries between October 2021 and June 2022. The meetings were audio or video recorded, transcribed and translated into English for qualitative framework analysis.Results We engaged 120 participants in the Collaborative User Boards. Proposed solutions targeted both provider and system levels. In all countries, fostering trusting relationships between vulnerable women and social or healthcare professionals, coupled with community outreach for awareness and access to testing was a consistent recommendation. Participants in Estonia, Denmark, France, Italy, Portugal and Romania advocated for tailoring healthcare services to meet the unique needs of vulnerable populations through a holistic approach. In Bulgaria and Romania, participants advocated for the need to secure free access, from screening to follow-up, and emphasised the need for organised screening with target population screening registries.Conclusion The study offers insights into stakeholders' recommendations for enhancing cervical cancer screening services for vulnerable women across seven European countries. Despite variations in the implementation level of population-based screening programmes, the imperative to optimise outreach and proximity work to improve cervical cancer screening resonated across all countries.